IUTAM Symposium on Asymptotics, Singularities and Homogenisation in Problems of Mechanics
DOI: 10.1007/1-4020-2604-8_27
|View full text |Cite
|
Sign up to set email alerts
|

Dynamics of Damage in Two-Dimensional Structures With Waiting Links

Abstract: The paper deals with simulation of damage spread in special structures with waiting links." These structures are stable against dynamic impacts due to their morphology. They are able to transform partial damage" through a large region, thereby dissipating the energy of the impact. We s i m ulate various structures with waiting links and compare their characteristics with conventional designs.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Publication Types

Select...
6
1
1

Relationship

6
2

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 3 publications
0
6
0
Order By: Relevance
“…Alternatively, one may account for a non-instant damage that corresponds to the differential equation for the accumulated damage (see Cherkaev and Zhornitskaya, 2003):…”
Section: Article In Pressmentioning
confidence: 99%
See 1 more Smart Citation
“…Alternatively, one may account for a non-instant damage that corresponds to the differential equation for the accumulated damage (see Cherkaev and Zhornitskaya, 2003):…”
Section: Article In Pressmentioning
confidence: 99%
“…It needs less assumptions, allows one to see the details of the damage, and to account for the high-frequency models that are ''invisible'' in the continuum limit. Some bistable-link chain models were considered in a number of works (see Troyankina, 1984, 1988;Puglisi and Truskinovsky, 2000;Slepyan, 2000Slepyan, , 2001Slepyan, , 2002Balk et al, 2001a,b;Charlotte and Truskinovsky, 2002;Ngan and Truskinovsky, 1999;Cherkaev and Zhornitskaya, 2003). In the present paper we consider a chain with waiting links, formulate the dynamic equations, and estimate the gap role in the resistance of the chain to quasi-static and dynamic extension.…”
Section: Introductionmentioning
confidence: 97%
“…These elements and their quasistatic behavior are described in [8]. Following [8], consider the link as an assembly of two elastic-brittle rods, lengths L and ∆(∆ > L) joined by their ends. The longer bar is initially slightly curved to fit.…”
Section: Elastic-brittle Waiting Elementsmentioning
confidence: 99%
“…The dynamic response of elastic-brittle bistable structures was also studied by . The response of chains of bistable structural elements under quasistatic and dynamic loading was investigated by Cherkaev and Zhornitskaya [2003]. The numerical results obtained showed that a chain of bistable links can withstand impact energy levels that are several times larger than for a conventional chain without bistable behavior.…”
Section: Introductionmentioning
confidence: 99%